(3JgPjH GdQjGSI hJQJjH GdSjGSIs - (3eMeO Hf Ydj Hf GdMSf GdbdYj,J (B630 (3g` s ((3CMeO Hf eMeO Hf GdXGaQ GdZSGfi s)
(3ChdgG (B:s
(3GdMeO ddg MeOkG cKjQkG hHYO agPG cJGH LeYJg ai JgPjH GdQjGSI hJQJjH GdSjGSI hLYdJg bSejf GdbSe GdChd efg jTJed OQQ ef fXGe GdaUMGA s
(3BNQgG (B:s
(3abGe GdCehi hbHd QCSg heVi MJi hUd eCefg hLGDg HcJGHg HSdGeJg hGddg CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280s
Keywords: (3GdSjGSI hGdGLJeGYs